Impacto socioambiental por el funcionamiento de la planta de asfalto municipal en familias del Barrio Rayito de Luz de Machala - Castillo Esmeraldas, Shirley Karelys; Minuche Ocaña, Nathaly Paulette (Machala: Universidad Técnica de Machala, 2022)
The present investigation was carried out in the Rayito de Luz neighborhood, where it was determined that the main problem is the operation of the asphalt plant that causes environmental pollution through the emanation of bad odors, noise, spillage of petroleum liquid, greenhouse gases, smoke, dust, generating discomfort and problems in the health of the inhabitants. In the Rayito de Luz neighborhood there are some of the aforementioned businesses that belong to families living in this sector, however, those that are near the asphalt plant have been affected with its operation. When the machine begins to work it produces dust that causes discomfort to both the houses and the premises around it, causing them to have to close during the days that there is more discomfort than usual, as is the case of the restaurants that cannot sell food in a polluted environment. It is important to mention that, the research is supported by the Constitution of Ecuador 2008, Ministerial Agreement NO.061 Reform of Book VI of the Unified Text of Secondary Legislation and Domains and Lines of Research of the UTMACH. The main objective was to determine the socio-environmental impacts generated by the operation of the municipal asphalt plant, in the inhabitants of the Rayito de Luz neighborhood of the city of Machala. It was based on the empirical-inductive epistemological approach, which at the time of the elaboration of the consistency matrix developed hypotheses that arose from the present problems, and which in turn was deduced, this allowed to reach empirical predictions, which were subjected verification and applied techniques of the same approach such as interview and structured observation. Consequently, the research is based on the sociological environmentalist currents, functionalism, these theories deal with social interactions and that each of the individuals can inhabit in comfort with their environment, in addition, they intend to analyze and organize the structures, changes and processes that occurred in society. On the other hand, the quantitative methodological process was applied since the research is based on numerical information for the collection of data that will serve in its measurement and explanation of the study of the research work. An observation guide was applied to demonstrate the reality of the place, in addition surveys were carried out to the members of the place to identify what the real problems are and to be able to reach clear conclusions. The survey of the inhabitants of the Rayito de Luz neighborhood helped to obtain the results of field research and in turn verify the most transcendental problems that were selected for the requirements matrix. The intervention proposal to be implemented to solve the existing problems in the neighborhood is the Design of social management strategies to improve the living conditions of the families of the Rayito de Luz neighborhood where it will be allowed to make inter-institutional agreements that commit institutions, neighborhood leaders and residents to work together for the strengthening and active participation that allow social strategies to help mitigate the problem socio-environmental to achieve well-being in the inhabitants and that they live in a calm and healthy environment.
La presente investigación se la realizó en el barrio Rayito de Luz, donde se determinó que el problema principal es el funcionamiento de la planta asfaltadora que ocasiona la contaminación ambiental a través de la eminencia de malos olores, ruido, derrame de líquido petrolizado, gases efecto invernadero, humo, polvo, generando molestias y problemas en la salud de los moradores. En el barrio Rayito de Luz existen algunos de los negocios antes mencionados que pertenecen a familias que viven en este sector, sin embargo, los que se encuentran cerca de la planta asfaltadora se han visto afectadas con su funcionamiento. Cuando la maquina empieza a trabajar produce polvo que causa molestia tanto a las viviendas como a los locales de su alrededor, causando que estos tengan que cerrar durante los días que se dan más molestias de lo habitual, como lo es el caso de los restaurantes que no pueden vender comida en un ambiente contaminado. Es importante mencionar que, la investigación está respaldada por la Constitución del Ecuador 2008, Acuerdo Ministerial NO.061 Reforma del Libro VI del Texto Unificado de Legislación Secundaria y Dominios y Líneas de Investigación de la UTMACH. El objetivo central consistió en determinar los impactos socioambientales generados por el funcionamiento de la planta asfaltadora municipal, en los habitantes del barrio Rayito de Luz de la ciudad de Machala. Se basó en el enfoque epistemológico empírico-inductivo, el cual al momento de la elaboración de la matriz de consistencia se desarrolló hipótesis que surgieron de los problemas presentes, y que a su vez se dedujo, esto permitió llegar a predicciones empíricas, que fueron sometidas a verificación y se aplicaron técnicas del mismo enfoque como son, entrevista y observación estructurada. Consecuentemente, la investigación se ampara en las corrientes sociológicas ambientalistas, funcionalismo, estas teorías se ocupan de las interacciones sociales y que cada uno de los individuos pueda habitar en confort con su entorno, además, pretenden analizar y organizar las estructuras, cambios y procesos acontecidos en la sociedad. Por otro lado, se aplicó el proceso metodológico cuantitativo puesto que la investigación está sustentada en información numérica para la recolección de datos que servirá en su medición y explicación del estudio del trabajo investigativo. Se aplicó una guía de observación para demostrar la realidad del lugar, además se realizó encuestas a los miembros del lugar para identificar cuáles son los problemas reales y poder llegar a conclusiones claras. La encuesta a los habitantes del barrio Rayito de Luz ayudo a obtener los resultados de investigación de campo y a su vez verificar los problemas más trascendentales que fueron seleccionadas para la matriz de requerimientos. La propuesta de intervención a implementarse para dar solución a la problemática existente en el barrio es el Diseño de estrategias de gestión social para mejorar las condiciones de vida de las familias del barrio Rayito de Luz en donde se permitirá realizar convenios interinstitucionales que comprometan a las instituciones, dirigentes barriales y moradores a trabajar en conjunto para el fortalecimiento y participación activa que permitan dar estrategias sociales ayuden a mitigar el problema socio-ambiental para lograr bienestar en los moradores y que habiten en un entorno tranquilo y sano.
Keywords: SOCIOAMBIENTAL; ESTRATEGIA; SALUD; LIDERAZGO